(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article explores the development of an Arduino-based smart fingerprint authentication mechatronic model for secure access control. The study highlights the integration of biometric technology with mechatronic modules to enhance security and automation. The proposed system utilizes fingerprint recognition, microcontrollers, and IoT-based connectivity to ensure efficient and reliable authentication. Experimental results demonstrate that the system significantly improves access control efficiency, reduces unauthorized access risks, and enhances operational reliability. The findings emphasize the high potential of mechatronic and biometric technologies in various security applications, suggesting future adaptability in different sectors, including smart homes, industrial security, and financial institutions.